Moxd1 Is a Marker for Sexual Dimorphism in the Medial Preoptic Area, Bed Nucleus of the Stria Terminalis and Medial Amygdala - Tsuneoka, Yousuke (Front Neuroanat, 2017)
The brain shows various sex differences in its structures. Various mammalian species exhibit sex differences in the sexually dimorphic nucleus of the preoptic area (SDN-POA) and parts of the extended amygdala such as the principal nucleus of the bed nucleus of the stria terminalis (BNSTpr) and posterodorsal part of the medial amygdala (MePD). The SDN-POA and BNSTpr are male-biased sexually dimorphic nuclei, and characterized by the expression of calbindin D-28K (calbindin 1). However, calbindin-immunoreactive cells are not restricted to the SDN-POA, but widely distributed outside of the SDN-POA. To find genes that are more specific to sexually dimorphic nuclei, we selected candidate genes by searching the Allen brain atlas and examined the detailed expressions of the candidate genes using in situ hybridization. We found that the strong expression of monooxygenase DBH-like 1 (Moxd1) was restricted to the SDN-POA, BNSTpr and MePD. The numbers of Moxd1-positive cells in the SDN-POA, BNSTpr and MePD in male mice were larger than those in female mice. Most of the Moxd1-positive cells in the SDN-POA and BNSTpr expressed calbindin. Neonatal castration of male mice reduced the number of Moxd1-positive cells in the SDN-POA, whereas gonadectomy in adulthood did not change the expression of the Moxd1 gene in the SDN-POA in both sexes. These results suggest that the Moxd1 gene is a suitable marker for sexual dimorphic nuclei in the POA, BNST and amygdala, which enables us to manipulate sexually dimorphic neurons to examine their roles in sex-biased physiology and behaviors.